Synthesis of Some 4’-O Substituted Derivatives of Natural Naringin and Their Biological Screening - Riaz, Tauheeda; Athar Abbasi, Muhammad; Rehman, Aziz-ur; Shahzadi, Tayyaba; Mohammed Khan, Khalid; Ashraf, Muhammad; Abida Ejaz, Syeda (Asian Journal of Chemistry, 2012)
This manuscript reports the synthesis of a series of new 4'-O-substituted derivatives of naringin (1) which is a naturally occurring flavanone glycoside isolated from the plant Rhynchosia pseudo-cajan Cambess. belonging to family of Papilionaceae. The structure of 1 was established through 1D and 2D NMR analysis and by comparison with its published data while its synthetic derivatives 3a-l, were characterized by 1H NMR spectra and all these were screened against four enzymes namely, acetylcholinesterase, butyrylcholinesterase lipoxygenase and chymotrypsin. Their antioxidant potential was also evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity and only 4'-O-ethyl naringin (3a) showed antioxidant potential (IC50 36.21 ± 0.32 μM). 4'-O-Ethyl naringin (3a), 4'-O-(2''''-phenylethyl) naringin (3f), 4'-O-(3''''-phenylpropyl) naringin (3g) and 4'-O-(p-fluorobenzyl) naringin (3i) were found to be moderate inhibitors of butyrylcholinesterase while naringin (1) itself, 4'-O-n-butyl naringin (3b), 4'-O-iso-propyl naringin (3d) and 4'-O-(N-3''''', 5'''''-dimethylphenyl-C-acetamido) naringin (3l) were identified as moderate inhibitors of lipoxygenase. Against chymotrypsin only 4'-O-(p-bromobenzyl) naringin (3h) was found to be a moderate inhibitor.